2014
DOI: 10.1007/978-3-319-09284-3_23
|View full text |Cite
|
Sign up to set email alerts
|

Improving Implementation of SLS Solvers for SAT and New Heuristics for k-SAT with Long Clauses

Abstract: Abstract. Stochastic Local Search (SLS) solvers are considered one of the best solving technique for randomly generated problems and more recently also have shown great promise for several types of hard combinatorial problems. Within this work, we provide a thorough analysis of different implementation variants of SLS solvers on random and on hard combinatorial problems. By analyzing existing SLS implementations, we are able to discover new improvements inspired by CDCL solvers, which can speed up the search o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…However, recent work shows that clause selection has a strong impact on the performance of WalkSAT algorithms and random selection is sometimes suboptimal. For example, breadth-first selection heuristics sometimes achieve better results (Balint et al 2014). Still, clause selection has to be rather simple because SLS solvers for SAT often perform several million moves per second.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent work shows that clause selection has a strong impact on the performance of WalkSAT algorithms and random selection is sometimes suboptimal. For example, breadth-first selection heuristics sometimes achieve better results (Balint et al 2014). Still, clause selection has to be rather simple because SLS solvers for SAT often perform several million moves per second.…”
Section: Methodsmentioning
confidence: 99%
“…Running some preliminary experiments showed that it is frequently better to select assertions that already have a high score (i.e., are almost satisfied). Given the results from (Balint et al 2014), it is likely that some diversification is beneficial as well. Therefore, we use a heuristic inspired by the field of bandit theory used in the UCB (Upper Confidence Bounds) algorithm (Agrawal 1995).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observation 1. (Balint et al 2014) During the focused random walk for uniform random k-CNF (k = 3, 4, 5, 6, 7) with ratio r k , about 90% break values encountered for variables within the chosen unsatisfied clauses are less than 5, while a constant fraction of break values can reach up to r k k/2.…”
Section: Theoretical Analysis For Random Formulasmentioning
confidence: 99%
“…Implementation affects the performances of SLS algorithm very much. The latest version of probSAT uses caching scheme with XOR technology [1], while WalkSAT in UBCSAT framework [4] and the latest version of WalkSATlm [2] are under non-caching implementation. In this section, we propose a more efficient implementation called separated-non-caching.…”
Section: Separated-non-caching Technologymentioning
confidence: 99%